Mechanisms Through Which Some Mitochondria-Generated Metabolites Act as Second Messengers That Are Essential Contributors to the Aging Process in Eukaryotes Across Phyla - Dakik, Paméla; Medkour, Younes; Mohammad, Karamat; Titorenko, Vladimir I. (Frontiers in Physiology, 2019)
Recent studies have revealed that some low-molecular-weight molecules produced in mitochondria can control aging and aging-associated pathologies in evolutionarily distant eukaryotes. These molecules are intermediates or products of certain metabolic reactions that are activated in mitochondria in response to specific changes in the nutrient, stress, proliferation or age status of the cell. After being released from mitochondria, these metabolites directly or indirectly change activities of a distinct set of protein sensors that reside in various cellular locations outside of mitochondria. Because these protein sensors control the efficiencies of some pro- or anti-aging cellular processes, such changes in their activities allow to create a pro- or anti-aging cellular pattern. Thus, mitochondria can function as signaling platforms that respond to certain changes in cell stress and physiology by remodeling their metabolism and releasing a specific set of metabolites known as "mitobolites". These mitobolites then define the pace of cellular and organismal aging because they regulate some longevity-defining processes taking place outside of mitochondria. In this review, we discuss recent progress in understanding mechanisms underlying the ability of mitochondria to function as such signaling platforms in aging and aging-associated diseases.